Promoting sustainable communities through affordable housing. A case study of Beirut, Lebanon - Mazzetto, Silvia; El-Khoury, Roula; Malkoun, Joanna (Frontiers in Sustainable Cities, 2024)
Promoting Sustainable communities aims at creating both environmentally and socially responsible living environments. This paper explores the role of affordable housing in promoting the long-term sustainability of a community within healthy living conditions by closely examining the relationship between affordable housing, urban development policies, and sustainability, with the capital of Lebanon, Beirut, serving as a case study. The first part of the paper focuses on the current building laws issued in the official newspaper in 2004 using a content analysis methodology to demonstrate the impact of the changes in the laws on the new morphology and social fabric of the city through the creation of a favorable environment for big developers, wealthy property owners, and real estate agencies and, at the expense of old city residents and low-income families. The second part of the paper uses the qualitative analysis methodology to justify the presence of large unused stock of residential units in Beirut, referring to information from multiple data sources selected based on their applicability to sustainable development, affordable housing, and urban planning in areas related to the case study, Beirut. This part then investigates the potential presented by this stock of residential units in Beirut to increase the supply of affordable housing and foster a sustainable community. This paper argues that the promoted vertical expansion of the city weighs heavily on the environment and fails to provide a diverse mix of housing units, excluding a significant portion of the community from the city. Alternative development models aligning with principles of sustainable development and challenging the current building laws can promote social inclusivity, reduce urban sprawl, and minimize environmental impacts associated with new constructions, thus preserving the city's physical and social fabric.